Adoption of Mobile Applications in Physiotherapy : role of influencing factors in physiotherapists’ adoption decision - Helle, Noora (fi=Turun yliopisto|en=University of Turku|, 2018)
Mobile health applications and their adoption is a very current field within health technology, with the number of mobile health applications reaching 325 000 in 2017. Distinguishing and marketing one’s offering has become a key challenge for companies producing mobile health applications. To combat this challenge, up to 14 % of mobile health application providers are targeting physicians as their main customers. This study extends the same model to physiotherapists through a case study of mobile application for physiotherapists. The research question is: “What is the role of different factors in physiotherapists’ mobile application adoption process?” Accordingly, the study approaches the subject through examining the different personal and environmental factors affecting the adoption decision: the role of personal factors, role of concern for patient and role of environmental factors (facilitating conditions, social influence). Concern for patient was a case-specific addition to the research questions, arising from the pilot interview. The study aims to construct a model explaining physiotherapists’ adoption of the mobile application by building a synthesis out of the prominent frameworks that explain technology acceptance: Technology Acceptance Model, Unified Theory of Acceptance and Use of Technology and Diffusion of Innovations. The synthesis formed was first tested by a pilot interview to improve the model. The model was then tested by performing a quantitative online questionnaire. The results of the questionnaire were analysed using factor analysis, variance analysis and multiple regression analysis. Results confirmed 6 out of 8 hypotheses, namely supporting the role of perceived value and ease of use for self, perceived value for patient, organizational support, social influence and the skilfulness of the physiotherapist as an IT user. The rejected hypothesis concerned ease of use for the patient and value for the physiotherapist’s organization. Based on the results of this study, the most significant factors in physiotherapists’ decision to use a mobile application are Perceived Ease of Use, Organizational Support and the Skilfulness of the physiotherapist as an IT user. This is somewhat contradictory with previous research, where consistently the perceived usefulness of the studied technology has been the most significant factor. It is possible, that the contradictory result is due to the fact, that value of the studied application is mainly for the patient, not for the physiotherapist themselves. A study with a larger sample size and testing for actual usage of the application instead of intention to use is recommended to explore the conclusions further.